In-Vitro Study of Osseointegration: Evaluating the Influence of Surface Modifications on Dental Implant Stability - Mohammed G. Sghaireen; Mohammad Khursheed Alam; Ahmed Azhari Salih Mohamedeissa; Jad Moriss Kazma (Wolters Kluwer Medknow Publications, 2024)
Background: Osseointegration is critical for the success of dental implants. Surface modifications of dental implants play a crucial role in enhancing osseointegration and implant stability. This in-vitro study aims to evaluate the influence of various surface modifications on dental implant stability. Materials and Methods: Dental implants with different surface modifications were prepared and subjected to in-vitro testing. Surface modifications included sandblasting, acid etching, and plasma spraying. Implant stability was assessed using resonance frequency analysis (RFA) and pull-out tests. Statistical analysis was performed to compare the stability of implants with different surface modifications. Results: The results showed that implants with sandblasted and acid-etched surfaces exhibited significantly higher stability compared with those with only a machined surface. The mean RFA values for sandblasted and acid-etched implants were 75 ± 5 and 80 ± 6, respectively, whereas machined implants recorded a mean RFA value of 60 ± 4. Similarly, pull-out tests demonstrated higher maximum tensile strengths for sandblasted and acid-etched implants compared with machined implants. Conclusion: Surface modifications, such as sandblasting and acid etching, significantly enhance dental implant stability in vitro. These modifications promote better osseointegration, which is crucial for the long-term success of dental implants in clinical practice.